Bruiser - Shusterman, Neal (New York : HarperTeen, 2010)
Inexplicable events start to occur when sixteen-year-old twins Tennyson and Brontë befriend a troubled and misunderstood outcast, aptly nicknamed Bruiser, and his little brother, Cody
Keywords: Family problems -- Juvenile fiction; Child abuse -- Juvenile fiction; Paranormal fiction; Twins -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Families -- Juvenile fiction; Interpersonal relations -- Juvenile fiction